The Literacy Hour - Stephen Machin; Sandra McNally (Institute for the Study of Labor (IZA), 2004)
In this paper, we evaluate the effect of the literacy hour in English primary schools on pupil attainment. The National Literacy Project (NLP) was undertaken in about 400 English primary schools in 1997 and 1998. We compare the reading and overall English attainment of children in NLP schools as compared to a set of control schools at the end of primary school education (age 11). We also compare the overall English performance of these children when they have reached the end of their compulsory education (age 16). We find a larger increase in attainment in reading and English for pupils in NLP schools as compared to pupils not exposed to the literacy hour between 1996 and 1998. We also find modest, but positive effects from exposure to the literacy hour that persist to age 16, as GCSE English performance is seen to be higher for children affected by the NLP introduction. Since there are gender gaps in English performance (in favour of girls), we consider whether the literacy hour has had a differential impact by gender. We find some evidence that at age 11, boys received a greater benefit than girls. Finally, we show the policy to be cost effective. These findings are of strong significance when placed into the wider education debate about what works best in schools for improving pupil performance. The evidence reported here suggests that public policy aimed at changing the content and structure of teaching can significantly raise pupil attainment.
Keywords: I2; 330; literacy hour; English; reading; Analphabetismus; Englisch; Bildungsniveau; Schätzung; Kosten-Nutzen-Analyse; Grossbritannien